Enchancing Vocabulary Mastery In 11th Grade Students Through Flashcard - Dzakia, Salma Fauza; Rahmawati, Henita; Suwandi (Lembaga Pengembangan Bahasa Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study explores the effectiveness of using flashcards to enhance vocabulary mastery among 11th-grade students at MAN 8 Jombang. The main objective is to identify how this visual learning tool can support students in expanding their vocabulary knowledge and improving language skills. Employing a qualitative descriptive research design, data were gathered through classroom observations, interviews, and documentation analysis. The results indicate that flashcards significantly contribute to students' vocabulary retention and comprehension by providing an engaging and interactive learning experience. Moreover, strategies such as integrating games, repetition, and personalized flashcards effectively motivate students and reinforce learning outcomes. This study underscores the potential of flashcards as a practical and versatile tool for EFL teachers in facilitating vocabulary acquisition and fostering student participation.